An Assessment of Strategic Management Practices and Organizational Failure in Private Medical Laboratories and Allied Health Centers in South-East Nigeria - Alexander Chinaza Aneke; Marcellinus Chukwuka Ihionu (Milestone: Journal of Strategic Management, 2026)
Despite rapid growth in Nigeria’s private medical diagnostic and allied health sector, many centers in South-East Nigeria continue to experience high failure rates driven by financial constraints, regulatory pressures, infrastructural deficits, technological demands, and broader socioeconomic challenges. This study investigates these multidimensional factors to inform policy development, strategic decision-making, and the long-term sustainability of private healthcare enterprises in the region. Adopting a historical research design, data were collected from ten purposively selected medical diagnostic centers in South-East Nigeria through the review of archival documents, institutional records, and relevant online sources. Content analysis was employed to identify recurring patterns and key themes. The findings indicate that facility closures are primarily associated with regulatory non-compliance, financial instability, and workforce attrition. Key challenges include operating without appropriate licensing, failure to adhere to quality management standards, shortages of essential supplies, high operational costs, particularly for electricity and equipment, and difficulties in retaining skilled personnel due to brain drain. These interrelated factors undermine operational efficiency and expose facilities to regulatory sanctions, financial losses, and reputational risks. The study further reveals that systemic weaknesses, including regulatory gaps, limited access to sustainable financing, and inadequate human resource capacity, threaten the viability of private healthcare providers in the region. It is recommended that policymakers strengthen regulatory enforcement, expand sustainable financing options, and implement targeted workforce retention strategies. This study contributes to the literature by contextualizing healthcare management challenges within a regional Nigerian framework.